2015
DOI: 10.1007/s10973-015-4694-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of pressure sintered alumina–graphene composites

Abstract: The work concerns the alumina-graphene materials sintered by two different pressure methods. The different particle sizes of graphene were used. The preparation route of the matrix-graphene mixture was discussed in the paper. The so-prepared compositions with different amount of graphene were hot-pressed and spark plasma sintered. The influence on uniaxial pressure during the sintering process on the microstructure was presented by the SEM microstructural observations and ultrasonic measurements. The material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…The increase in thermal conductivity, thermal diffusivity, and heat capacity with the increase in sintering temperature and sintering time is due to the increase in relative density and the decrease in porosity as explained above. This trend is in agreement with what published in literature [34]. In addition, the increase in crystallite size and the decrease in sub-grain boundaries contribute to the increase in these thermal properties.…”
Section: Resultssupporting
confidence: 93%
“…The increase in thermal conductivity, thermal diffusivity, and heat capacity with the increase in sintering temperature and sintering time is due to the increase in relative density and the decrease in porosity as explained above. This trend is in agreement with what published in literature [34]. In addition, the increase in crystallite size and the decrease in sub-grain boundaries contribute to the increase in these thermal properties.…”
Section: Resultssupporting
confidence: 93%
“…Cowan's model was used for thermal diffusivity calculation in the case of single-layer analysis. This method gives the possibility to measure thermal diffusivity and heat capacity with high precision and is relatively simple in sample preparation and interpretation of results [11][12][13][14]. The analysed samples were placed in the sample carrier in such a way that their original surface (for example, rough top surface of NiCrAlY coating) was faced down.…”
Section: Methodsmentioning
confidence: 99%
“…As is known that graphene is a single carbon atom thick two-dimensional material that can be effectively utilized as a nanofiller for improving the mechanical, thermal, optical, and electrical properties of composites even at a low content, as many reports at home or abroad indicated [16][17][18]. Bao et al [19] found that with the masterbatch-melt-blending technique, graphene can be well dispersed and exfoliated in polystyrene as thin layers and the fire safety properties of PS were obviously improved, getting an increased thermal degradation temperature (18°C, PS/Ni-Gr-2), decreased peak heat release rate (40 %, PS/Zr0-Gr-2), and reduced CO concentration (54 %, PS/Ni-Gr-2).…”
Section: Introductionmentioning
confidence: 99%